The death penalty : opposing viewpoints - Winters, Paul A. (San Diego, CA : Greenhaven, 1997)
Presents both sides of the issues surrounding the topic of capital punishment.
Includes bibliographical references and index.
10-A.
Keywords: Capital punishment; Capital punishment; Criminal law